Metasomatized lithosphere–asthenosphere interaction during slab roll-back: Evidence from Late Carboniferous gabbros in the Luotuogou area, Central Tianshan - Tang, G.; Wang, Q.; Wyman, D.; Li, Zheng-Xiang; Xu, Y.; Zhao, Z. (Elsevier BV, 2012)
Late Carboniferous igneous rocks are widespread in the western Tianshan, but the tectonic settings for these rocks remain controversial. We report a plagioclase 40Ar/39Ar age, and geochemical, Sr–Nd isotope and LA–ICPMS clinopyroxene trace element data for gabbros in the Luotuogou region. The tholeiitic Luotuogou gabbros give a Late Carboniferous (312 ± 1 Ma) 40Ar/39Ar age and are characterized by high and variable εNd(t) values ranging from + 3.7 to + 7.8. They have geochemical features of both intra-plate and island arc magmatic rocks, i.e., relatively high TiO2 (0.6–2.2 wt.%), Nb (4.2–24 ppm) and Zr (51.4–283 ppm) contents combined with variable and slightly high Nb/La ratios (0.24–1.8, mostly > 0.7), and negative to positive Nb anomalies. The gabbros contain zoned clinopyroxenes, with Mg- and Cr-rich cores. Their parental magmas, as calculated using trace element data from Cr-rich (> 3000 ppm) clinopyroxene cores and clinopyroxene/basaltic liquid partition coefficients, show enrichments in incompatible elements, and prominent negative to slightly positive Nb anomalies, indicative of the influence of subduction-related compositions in their mantle source. These features indicate that the Luotuogou gabbros were most likely formed by interactions between asthenospheric and metasomatized lithospheric mantle. They were most plausibly formed by mixing between the asthenospheric mantle-derived and metasomatized lithosphere mantle-derived melts. Mixing was the result of asthenosphere upwelling triggered by roll-back of the subducted Paleo-Junggar Oceanic Plate rather than mantle plume-related rifting or post-collisional break-off during the Late Carboniferous.